Dreaming Out Loud : African American Novelists at Work - Porter, Horace A., 1950- (Book collections on Project MUSE., 2015)
Bois, Ralph Ellison, Ernest Gaines, Chester Himes, Langston Hughes, Zora Neale Hurston, Charles Johnson, James Weldon Johnson, Gayl Jones, Terry McMillan, James Alan McPherson, Toni Morrison, Walter Mosley, Ishmael Reed, Martha Southgate, Alice Walker, Margaret Walker, John Edgar Wideman, Richard Wright.